Knowledge, attitude and practices towards COVID-19 among healthcare workers of Karnataka, India: a cross-sectional survey - Verma, Satendra Kumar; Kumar, D. Sunil; Khanum, Rufia Shaistha; N., Chandan; Narayanmurthy, M. R. (International Journal Of Community Medicine And Public Health, 2020)
Background: COVID-19 is a Public health emergency of international concern which has affected over 213 countries infecting millions across the globe and also affected the economy worldwide. This study was conducted in Healthcare Workers as they are the frontline warriors in fighting this pandemic and their knowledge, attitude and practices towards the disease are valuable. Methods: Online cross sectional study was conducted on Healthcare Workers. A self-administered Google form was used to collect the data through social media. Data was analyzed using MS Excel. P<0.05 was considered statistically significant obtained using SPSS version 22. Results: The mean age among the participants was 30.7±9.9 years. Majority were in the age group of 20-30 years (60.9%), followed by 31-40 years (18.9%), 41.-50 years (9.1%) and >50 years (5.4%). 46.3% of the participants were females and 53.0% were males. 37.1% were doctors, 14.0% are nurses and 46.9% are paramedical staff. In the present study, Mean knowledge score is 5.86±1.32, mean attitude score is 6.48±0.93 and the mean practice score is 4.60±0.79, thus 95.7% of the participants have good knowledge and attitude, where as 90.3% have good practices towards COVID-19. Conclusions: The HCWs of Karnataka have good knowledge, positive attitude and good practices. To further improve their preparedness and response towards infectious diseases and pandemics mandatory training programs can be introduced, as such programs enhances knowledge and boosts confidence among HCWs which is very crucial in medical as well as public health emergencies.